PENGARUH PENGAWASAN TERHADAP IMPLEMENTASI SIKOPROL DI DINAS KOPERASI, UKM, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN SUMEDANG - Febianti, Fepi; Kania, Anisa Novianty Dwi; Sadiah, Evi Fatimus; Ramadhan, Ilham; Purnama, Nita; Cahyadi, Sandi (LPPM UNSAP & FISIP UNSAP, 2023)
An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper. Information technology really helps a person, business entity or legal entity in carrying out their work and duties more quickly and easily. One legal entity that uses information technology to support the needs of carrying out its duties is Bidang Koperasi in Dinas Koperasi, UKM, Perdagangan dan Perindustrian of Sumedang Regency by creating an application called SIKOPROL. The implementation of the Sikoprol application can affect Cooperative supervision so that the process of achieving Organizational goals can be achieved properly. The purpose of this study was to determine the implementation of the SIKOPROL application and controlling of Koperasi, to determine the relationship between the Implementation of the SIKOPROL Application and Controlling of Cooperatives and to determine the effect of the Implementation of the SIKOPROL Application on Supervision of Cooperatives in Bidang Koperasi in Dinas Koperasi, UKM, Perdagangan dan Perindustrian of Sumedang Regency. This research uses descriptive analysis method with a quantitative approach and the types of statistics used are descriptive statistics with saturated sampling techniques. The number of samples studied were 15 respondents. The analysis used includes validity test, reliability test, normality test, percentage calculation, correlation coefficient test, significance test and coefficient of determination test. Based on the research results, it is known that the implementation of the SIKOPROL application. Dinas Koperasi, UKM, Perdagangan dan Perindustrian iniSumedang Regency is already in good criteria with analysis results reaching 90.67%. Likewise, Controlling of Koperasi is in good criteria with the results of the analysis reaching 86.67%. From the correlation analysis, it was obtained a correlation value of 0.676 which indicates a positive and significant relationship between the implementation of the SIKOPROL application and Controlling of Koperasi. From the analysis of the coefficient of determination it is known that the SIKOPROL Implementation variable has an influence on Cooperative controlling of 48.5%. The remaining 52.5% is influenced by other factors not examined in this study.